CAREER ASSESSMENT THAT IS TAUGHT IN PUBLIC AND PRIVATE SCHOOLS OF THE CITY OF LIMA - Frisancho León, Augusto Emilio (2014)
The main objective of this study was to determine if there are differences in the manner of carrying out vocational guidance among public and private schools of the city of Lima. The study sample consisted of 244 subjects, 98 men and 146 women, students of University High of San Marcos Center for Special Cycle 2011-2012. The mean age was 16.3 years. For the realization of this research was developed and implemented the Rating Scale Vocational Guidance (EEOV), an instrument based on the model of vocational guidance Manuel Alvarez et al. (1994). The results indicate that the group of public school no different private schools group in the overall score of the scale. The results also indicate that the group of public school no different private schools group in the dimensions of life project and information about yourself, information about careers, analysis, reflection and guidance, advice, and Decision-making and career choice. Yes there is a statistically significant difference in the dimension information Peruvian educational system. Apparently, private schools offer better information to their students about the Peruvian educational system that offered by public schools. Vocational programs that are taught in the public schools of the city of Lima would have to place greater emphasis on this aspect.